AUTOMATION AND PROSPECTS FOR THE USE OF MAN-MADE WASTE FROM METALLURGY AND ENERGY ENTERPRISES (CIS COUNTRIES) - К. Akishev; L. Akishev L; Shyngisbayev A (Modern Scientific Method, 2026)
The use of man-made waste from metallurgy and energy enterprises is an urgent problem for the CIS countries due to the significant accumulated volumes and low share of processing and the insufficient level of automation of their processing. The need for a solution is due to the need to involve secondary resources in industrial turnover and the transition to a circular economy